Benefits of Applying the 5S Model to Industrial Companies in Peru - Díaz Garay, Bertha Haydeé (2020)
The following study aims at analyzing the benefits of applying the 5S Model to Peruvian industrial companies by means of descriptive, non-experimental, mixed methods research on Peruvian industrial companies that have won the 5S National Award. Techniques such as surveys and interviews were employed. This study found correlation between implementing the 5S Model and management models such as quality, environment and occupational health and safety. The research concluded implementing the 5S on the studied organizations has generated improvements in the work environment, waste reduction, worker’s performance and reputation. Keywords – 5S, Continuous Improvement, Waste Reduction, Lean Manufacturing, Management Models.